Perceptual crossing: the simplest online paradigm - Auvray, Malika; Rohde, Marieke (Frontiers in Human Neuroscience, 2012)
Researchers in social cognition increasingly realize that many phenomena cannot be understood by investigating offline situations only, focusing on individual mechanisms and an observer perspective. There are processes of dynamic emergence specific to online situations, when two or more persons are engaged in a real-time interaction that are more than just the sum of the individual capacities or behaviours, and these require the study of online social interaction. Auvray et al.’s (2009) perceptual crossing paradigm offers possibly the simplest paradigm for studying such online interactions: two persons, a one-dimensional space, one bit of information, and a yes/no answer. Despite, or maybe because of its simplicity, this study has provoked a lot of resonance in different areas of research, including experimental psychology, computer/robot modelling, philosophy, more recently psychopathology, and even in the field of design. In this article, we review and critically assess this body of literature. We give an overview over work on the perceptual crossing paradigm, both concerning behavioural experiments and computational agent modelling, and review the different contexts in which it has been referred to. We discuss the controversy about the possible constitutive role of perceptual crossing for social cognition and other theoretical contexts in which the research has been cited, offering our own interpretation. We conclude with an outlook on future research possibilities, in particular those that could elucidate the link between online interaction dynamics and individual social cognition.